Genetic polymorphism of milk protein and its effects on milk composition traits in Muzaffarnagari sheep - MANDAL, AJOY; KUMAR, D; ROUT, P K; YADAV, N K; ROY, R (The Indian Journal of Animal Sciences, 2011)
The electrophoretic pattern revealed the presence of three aS1- casein alleles, viz. (lSI-CnA, ascCnE and (XSI-CnF in the milk samples of Muzaffamagari sheep. The frequency of predominant aSI-CnE locus and rare (XSI-CnF variant in this population were 0.38 and 0.01, respectively, where the frequency of null allele for this locus (asi-CnO) was 0.37. All the loci except -Cn, -lactoglobulin and a- lactalbumin locus in the population showed the presence of null allele. No polymorphic patterns were observed at a S2-’ - and K casein locus in this study. The - lactoglobulin loci showed the presence ofAand Bvariants on the gel. The a-lactalbumin loci revealed the monomorphic form in the population. The study also showed that CXS1 - casein variant had only significant effect on casein content of milk and none of these milk protein variants had significant effect on total protein content of milk in this breed. Â